Biodegradation of expanded and extruded polystyrene with different diets by using Zophobas atratus larvae (Coleoptera: tenebrionidae) - Hoe Tay, Jun; Asib, Norhayu; Abd Aziz, Nor Azwady; Hun Tan, Geok (Universiti Putra Malaysia, 2023)
Polystyrene waste polluted the environment and poses a significant health risk to humans, animals and the marine ecology. This study aims to evaluate the effectiveness of degradation on expanded and extruded polystyrene with different diets using superworms (Zophobas atratus larvae) obtained in Malaysia. The growth and development of the larvae after consumption of expanded (EPS) and extruded (XPS) polystyrene, and the gut's microbial community changes in response to high polystyrene consumption diets were also identified. The oatmeal, wheat bran, and cornmeal were used as supplements diets showed significantly enhanced EPS and XPS consumption and degradation compared to sole diet treatment. Gel permeation chromatography (GPC) was carried out using egested frass of Z. atratus larvae to characterize depolymerization of EPS and XPS which indicated significant reduction in both Mn and Mw of EPS and XPS. The highest reduction occurred in the presence of co-diet oatmeal. 1H NMR and FTIR analyses results indicated functional group changes and chemical modification occurred with depolymerization and partial oxidation of EPS and XPS. The larvae length increased, while the number of instars and duration of larvae became shorter with the addition of supplements diets. Oatmeal is predominantly effective among other supplements in assisting Z. atratus larvae on EPS and XPS degradation. The results of this study support ubiquity of PS biodegradation in Z. atratus, and the next generation sequencing studies. Kluyvera sp., Klebsiella sp. and Enterobacter sp. were found strongly associated in degrading EPS and XPS polystyrene with oatmeal as a supplemental diet.